Bahala Na as an Expression of the Filipino's Courage, Hope, Optimism, Self-efficacy and Search for the Sacred - Menguito, Ma. Ligaya (Archīum Ateneo, 2010)
The literature on bahala na has largely focused on its negative qualities such as its seeming equivalence with dependence and fatalism. However, bahala na actually finds its roots in the spiritual core of the value system of the Filipinos, hence should be an expression of something desirable and worthy. This research aimed to refocus our attention and explore the positive side of bahala na in the context of five strengths: hope, self-efficacy, optimism, courage, and search for the sacred. Two focus group discussions were conducted in Metro Manila involving 11 and 13 participants respectively coming from a middle class village and an urban poor community. Thematic analysis was used to examine the data. Results show that whilebahala na retains some of its more popular negative aspects, the predominant view suggests a rational assessment of one’s resources and the situation which leads to a series of goal-attainment activities. It was also discovered that socio-economic status is a factor in the way bahala na was used in the context of hope, self-efficacy, and search for the sacred.